2019
DOI: 10.1152/ajpheart.00610.2018
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Notch signaling by soluble Dll4 decreases vascular permeability via a cAMP/PKA-dependent pathway

Abstract: The Notch ligand delta-like ligand 4 (Dll4), upregulated by VEGF, is a key regulator of vessel morphogenesis and function, controlling tip and stalk cell selection during sprouting angiogenesis. Inhibition of Dll4 results in hypersprouting, nonfunctional, poorly perfused vessels, suggesting a role for Dll4 in the formation of mature, reactive, functional vessels, with low permeability and able to restrict fluid and solute exchange. We tested the hypothesis that Dll4 controls transvascular fluid exchange. A rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Delta-like ligand 4 (DLL4), one of the ligands of Notch receptors, is predominantly expressed in the endothelial cells and has been shown to play a pivotal role in regulating tumor angiogenesis [38][39][40][41][42][43][44][45]. Some studies reveal a role for DLL4 in tumorigenesis in several cancers, including T acute lymphoblastic leukemia (T-ALL) [46], and glioblastoma [47] etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delta-like ligand 4 (DLL4), one of the ligands of Notch receptors, is predominantly expressed in the endothelial cells and has been shown to play a pivotal role in regulating tumor angiogenesis [38][39][40][41][42][43][44][45]. Some studies reveal a role for DLL4 in tumorigenesis in several cancers, including T acute lymphoblastic leukemia (T-ALL) [46], and glioblastoma [47] etc.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reveal a role for DLL4 in tumorigenesis in several cancers, including T acute lymphoblastic leukemia (T-ALL), and glioblastoma etc. [37][38][39][40][41][42][43][44][45][46][47]. DLL4 is one of the ligands of Notch 1.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that activation of Notch signaling by soluble Dll4 (sDll4) decreases vascular permeability, mainly due to an increased expression of VE‐Cadherin at intercellular junctions, and thus we used an adenovirus (Ad.sDll4) to promote early vessel maturation in the hindlimb ischemia mouse model, in order to assess its effect on recovery of blood flow. Firstly, to confirm that sDll4 was able to induce angiogenesis as well, we used an in vitro angiogenesis assay, where co‐cultured fibroblasts and ECs were treated with adenovirus‐conditioned media, stained, and imaged (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Ad.sDll4 gives rise to the over‐expression of the extracellular portion of Delta‐like ligand 4, which is sufficient to activate Notch signaling, nuclear translocation of NICD, and Hes/Hey upregulation in ECs …”
Section: Methodsmentioning
confidence: 99%
“…We failed to detect any association of serum Dll4 levels with organ involvement other than ILD and vascular manifestations (Table 1). Soluble Dll4 serves as an activator or inhibitor of neovascularization in a context-dependent manner in vivo and in vitro, 3,4 but serum Dll4 levels did not correlate with any vascular complications, suggesting the minimal effect of soluble Dll4 on SSc vasculopathy. On the other hand, the association of serum Dll4 levels with ILD suggests the potential role of Notch/Dll4 pathway in CD4 + T-cell differentiation in the lung.…”
mentioning
confidence: 92%